Hemoglobin variants shape the distribution of malaria parasites in human populations and their transmission potential. Issue 1 (December 2017) - Gonçalves, Bronner; Sagara, Issaka; Coulibaly, Mamadou; Wu, Yimin; Assadou, Mahamadoun; Guindo, Agnes; Ellis, Ruth; Diakite, Mahamadou; Gabriel, Erin; Prevots, D.; Doumbo, Ogobara; Duffy, Patrick
Abstract Hemoglobin variants C and S protect against severe malaria but their influence on parameters not directly linked to disease severity such as gametocyte carriage and infection chronicity is less well understood. To assess whether these infection-related phenotypes depend on the host hemoglobin genotype, we followed 500 Malian individuals over 1–2 years and determined their parasitological status during monthly visits and incidental clinical episodes. While adults heterozygous for hemoglobin S mutation were less often parasitemic compared to AA adults (odds ratio [OR] 0.50 95% confidence interval [CI] 0.31–0.79, P = 0.003), schoolchildren (but not toddlers or adults) with AC genotype carried parasites, including gametocytes, more often than their AA counterparts (OR 3.01 95% CI 1.38–6.57, P = 0.006). AC children were also likelier to be parasite-positive during the dry season, suggesting longer infections, and were more infectious in mosquito skin feeding assays than AA children. Notably, AC school-aged children, who comprise 5% of the population, harbor a third of infections with patent gametocytes between May and August, when transmission transitions from very low to intense. These findings indicate that schoolchildren with hemoglobin C mutation might contribute disproportionately to the seasonal malaria resurgence in parts of West Africa where the HbC variant is common.